(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Teacher education framework is a significant vehicle to work on the nature of school education. The renewal and fortifying of the teacher education framework is an incredible method for the upliftment of educational guidelines in the country. There are many issues that need pressing consideration for working on the nature of teacher education program. One of them is the need of advancements in teacher education program. Imaginativeness implies the capacity to think past the limits and make something which is not the same as that which as of now exists. Without advancements, no advancement is conceivable. Teachers must be inventive and their prepping needs to begin from their preparation establishments. Advancements in teacher education incorporate IT proficiency, intuitive video chatting and so on NPE expressed The current arrangement of teacher education should be updated or patched up.